Recovery of Oculomotor Nerve Palsy after Endovascular and Surgical Treatment of Posterior Communicating Artery Aneurysms: A Single Institutional Experience - Mak, Siu Kei David (Asian J Neurosurg, 2018)
INTRODUCTION: Surgical oculomotor nerve palsy(ONP), defined by ptosis, ophthalmoplegia, diplopia and pupillary dilatation, is associated with intracranial aneurysms, especially posterior communicating artery (PcomA) aneurysms. Treatment of PcomA aneurysms include endovascular coiling and surgical clipping. This study retrospectively compared the recovery of ONP in patients who underwent endovascular coiling or surgical clipping. METHODS: A retrospective review of patients with PcomA aneurysms who presented with ONP between 1998 and 2012 in the National Neuroscience Institute, Singapore, was performed. Inclusion criteria included adult patients of age above 21 who have radiologically confirmed PcomA aneurysms with presentation of ipsilateral ONP. The aneurysms may be unruptured or ruptured with WFNS grade 2 subarachnoid hemorrhage (SAH) or better. Only patients with completely surgically or endovascularly obliterated PcomA aneurysms with regular follow-up are included. RESULTS: A total of 22 patients were recruited. They were treated by either endovascular coiling or surgical clipping. The two groups of patients were demographically comparable, with 11 patients in each arm. 13 (59%) patients had unruptured aneurysms and 9 (41%) had WFNS grade 2 or better SAH. 13 (59%) patients presented with complete ONP and 9 (41%) had partial ONP. 64% of patients who underwent surgical clipping had resolution of ONP completely, compared to 18% of endovascularly coiling (P = 0.03) at 1-month follow-up. CONCLUSION: Compared to endovascular coiling, surgically clipped PcomA aneurysms are associated with a faster rate of full recovery of ONP.